Desain UI/UX Aplikasi SEWA Menggunakan Metode Design Thinking - Purwati, Nani; Syukron, Akhmad; Attabi, Kuffi; Sawwara, Sawwara (Universitas Bina Sarana Informatika, 2023)
Stunting in toddlers is a child problem that is still a concern for the government. The government has implemented various policies in an effort to reduce cases of stunting under five in Indonesia. In line with increasingly advanced and rapid technological developments, this study aims to design the UI/UX of an early stunting detection application for toddlers to help posyandu cadres measure and detect early cases of stunting and malnutrition in toddlers. The research method used in UI/UX development is the Design Thinking method. While the application testing method uses the SEQ method. The results of usability testing use the SEQ method with a total of 6 respondents consisting of officers and parents, obtaining a SEQ value of 6.26. The test results above 5.5 mean that this application is easy to use and can provide solutions to existing problems. The Design thinking method is proven to be able to produce a good interface according to user needs.Keywords: UI/UX; User Interface; User Experience; Design Thinking; SEQ.